O direcionamento socioambiental da usina hidrelétrica binacional de Itaipu - Ostrovski, Dalésio (2013)
The present thesis aims to discuss about the environmental policy developed by the Itaipu Bio-National Hydroelectric Dam, in the Parana 3 basin, by the environment program denominated Cultivating the Good Water, its possible influences on the ordering and reordering of the territory and the social and environmental improvement of the analyzed space. To reach such goals we raised issues that sustain an environmental policy as the growing process and economic development that makes a sustainable development and the characterization of the socio-environmental responsibility while strategic administrative process in the business environment. We also analyzed the historical process of the Parana State West Region and the socio-spatial reflexes created by the dam implementation. At last, we developed an extensive field work followed by the data analysis that allowed to prove the dam´s concrete action dam related to the implementation program, the sociopolitical influence, the interference in the process of the space ordering and reordering.